A Model And Field Study Of Tunnel Pre-Reinforcement - Gregory E. Korbin (Society for Mining, Metallurgy & Exploration, 1976)
The effectiveness of pre-reinforcement as an immediate stabilization measure as well as its contribution to the permanent stabilization of a tunnel were studied through the use of physical (Figure 1) and numerical models (1). Physical models were designed for the investigation of two pre-reinforcement systems: first, reinforcing far ahead of the main excavation (Figure 2); second, spiling reinforcement ahead of the face (Figure 3). In both cases, the use of reinforcement was responsible for permanently stabilizing an otherwise unstable opening. Data from the physical models were used to calibrate a numerical model from which additional information on long term behavior, methods to account for the capacity of a pre-reinforcement system, and the mechanisms involved were ascertained. These studies indicated that pre-reinforcement can stabilize a rock mass effectively as it reduces deformations and thereby deterioration due to strain softening, provides rock mass confinement leading to increased available strength, and maintains rock arch continuity allowing for increased tangential stress in the immediate vicinity of the opening. Field studies verified the capacity of spiling reinforcement to restrain initial deformations.